(untitled) (Research, Society and Development, 2021)
The supervised teaching internship consists of an experience lived by a beginning student accompanied by a qualified and experienced teacher in the area, being then considered an essential practice for the formation of new professional educators, to which the intern shows his knowledge, autonomy and creativity. Thus, this work aimed to develop an experience report of a master’s student with a bond in a Graduate Program in Biotechnology. The internship was developed in the Medicine course at the Federal University of Delta do Parnaíba. It was intended for the preparation of theoretical classes as well as the development of exercises, both within the field of human physiology and the activities developed were in the disciplines of Basics of Biological Processes I and II. In addition, all activities developed were supervised by the teacher responsible for the curriculum components. It is noteworthy that the period of the supervised teaching internship was during the first semester of 2021, when classes are in a remote form due to the current pandemic affected by the new coronavirus. To this end, some digital platforms for synchronous and asynchronous meetings were taken advantage of, respectively, Google Classroom and Google Meet. As a result, the supervised teaching internship was satisfactory and contributed to this teaching-learning experience, as it was allowed to establish a professional correlation as a teacher so that it can be applied in the future in the career that the candidate intends to follow in higher education. In addition, it was possible to understand how higher education professionals should behave in different situations, and always seek alternatives.